A study on knowledge and preventive practices related to Avian Influenza among Higher Secondary School Students of Rajbiraj Municipality, Nepal - Jitendra Kumar Sah; Sudip Chiluwal; Sawan Kumar Yadav; Durganand Jha (Al Ameen Medical College, 2017)
Background: Avian influenza is considerable global public health threat today, so prevention and control depends on the knowledge and protective behaviors of the general population as well as high risk groups. Objectives: The present study was conducted to determine the knowledge and preventive practices related to avian influenza among higher secondary school students. Materials and Methods: A community based cross-sectional study was conducted among 158 higher secondary school students using pre-tested structured questionnaire administered at interview. Frequency and percentage were calculated. Ethical clearance, informed consent and assent were taken from the concerned authority. Results: Majority (43.03%) participants were of age 17 years and more than two thirds (70.25%) were male. Main source of information on avian influenza was television (51.27%). More than three quarters (87.34%) study participants were aware that avian influenza can be transmitted from bird to human while (64.55%) knew that transmission could be from eating infected meat. Preventive practices adopted include avoid contact with sick or dead birds (41.13%) and hand washing (40.63%). Conclusion: This study emphasizes the need for intensified health education program among higher secondary school students in order to deal with this serious public health havoc.